2003
DOI: 10.1002/j.1939-4640.2003.tb03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chromosome Breakage and DNA Integrity in Sperm: An Investigation of Remote Semen Collection Conditions

Abstract: Collection of ejaculated semen at a remote site (outside of the laboratory) would facilitate participation rates and geographic diversity in reproductive epidemiology studies. Our study addressed concerns that remote collection and overnight mail return might induce chromosome/DNA damage. We collected semen from 10 healthy men. Part of each sample was snap frozen in liquid nitrogen and the rest held at 22 +/- 1 degrees C for 24 hours in a transport container (simulating ambient temperature during overnight ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 38 publications
(49 reference statements)
0
21
0
2
Order By: Relevance
“…These incorporated labeled nucleotides can be detected in spermatozoa by FC, fluorescence microscopy or light microscopy. 96 TUNEL can simultaneously detect single-and double-strand breaks. By TUNEL the degree of DNA damage within a cell cannot be quantified, which only reveals the number of cells within a population with DNA damage An advantage of the TUNEL assay is its application in FC, 97 although DomĂ­nguez-Fandos et al 98 found 2.6 times greater sperm damage by FC than that of fluorescent microscopy, thus suggesting that it may overestimate damage.…”
Section: Sperm Intactnessmentioning
confidence: 99%
“…These incorporated labeled nucleotides can be detected in spermatozoa by FC, fluorescence microscopy or light microscopy. 96 TUNEL can simultaneously detect single-and double-strand breaks. By TUNEL the degree of DNA damage within a cell cannot be quantified, which only reveals the number of cells within a population with DNA damage An advantage of the TUNEL assay is its application in FC, 97 although DomĂ­nguez-Fandos et al 98 found 2.6 times greater sperm damage by FC than that of fluorescent microscopy, thus suggesting that it may overestimate damage.…”
Section: Sperm Intactnessmentioning
confidence: 99%
“…Some of these variants are widely utilized, for instance the use of formaldehyde to fix semen samples or the use of fluorescence microscopy (the most available technology to reveal fluorescence) to score samples. However, differences in the TUNEL assay include: (i) preparation, fixation, and permeabilization of samples, (ii) protocols for labeling DNA breaks, (iii) technologies to detect fluorescence, and (iv) methods to analyze flow cytometric data (Table I) [Young et al 2003;Zhang et al 2008], to promote nuclei decondensation.…”
Section: Existing Variants Of the Tunel Procedures Greatly Affect Measmentioning
confidence: 99%
“…By reviewing studies conducted in raw semen from similar groups Muciaccia et al 2007;O'Flaherty et al 2008;Cohen-Bacrie et al 2009;Tunc et al 2008;Martin et al 2005Formaldeyde d Muratori et al 2003Caglar et al 2007;Tarozzi et al 2009;DomĂ­nguez-Fandos et al 2007;Young et al 2003;Avendañ o et al 2009a and2009b;Stronati et al 2006;Ramos et al 2008;Tesarik et al 2004 Permeabilization with detergents Absent Martin et al 2005;O'Flaherty et al 2008;Young et al 2003;Said et al 2006Present e Chohan et al 2006Aoki et al 2006;Caglar et al 2007;Varum et al 2007;Muratori et al 2008a andTunc et al 2008;Frydman et al 2008;Avendañ o et al 2009a and2009b Labelling Direct labeling f O'Flaherty et al 2008;Zhang et al 2008;Aoki et al 2006;Torregrosa et al 2006;Young et al 2003;Muratori et al 2008a;.Greco et al 2005;Paasch et al 2004;Brugnon et al 2006;Donnelly et al 2000 Indirect labeling g Varum et al 2007;Sergerie et al 2005;P...…”
Section: Comparing Flow Cytometry and Fluorescence Microscopy For Spementioning
confidence: 99%
“…Transport or storage of liquid human semen overnight, cooled or at room temperature after extension in one of several buffers, including those formulated with hen's egg yolk, protects sperm motility and function [18,[21][22][23][24][25][26][27][28]. According to Manjunath [29], the protective effect of hen's egg yolk or milk-based extenders appears to be due to low density lipoprotein (LDL) components in the buffer that competitively bind with and scavenge a family of proteins known, in hoof stock, as binder of sperm (BSP) proteins, reducing the sensitivity of the sperm membrane to cooling, and protecting/ replacing cholesterol within the sperm membrane.…”
Section: Discussionmentioning
confidence: 99%